INDUSTRI PERBANKAN YANG TERKONSENTRASIAPAKAH TETAP DAPAT BERKOMPETISI?KASUS PERBANKAN SYARIAH - Sancoko, Sancoko (UI Scholars Hub, 2013)
This paperdiscusses theconditions ofcompetitionbankingindustryin Indonesia, especiallyIslamic Bankingentity. Islamic Bankbecame the objectof research because significant growth in industrial banking.This studyuses a quantitative approachwith adescriptivedesign. Source ofdata used fromindividualbank's annual reporton the websiteof BankIndonesia fromthe period 2008-2011. Tomeasureaspects ofcompetition Islamic Bankingusing Panzar&Rosestatisticmethods. Results of studyshowed thatIslamic banking came into condition of monopolisticcompetitition structure.